HUBUNGAN ANEMIA DENGAN KEJADIAN MALARIA PADA IBU HAMIL DI WILAYAH PUSKESMAS WAENA - Muji Lestari; Yeni Wardhani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Papua Province was one of the malaria endemic areas. Malaria infection can affect the morbidity and mortality of the fetus and pregnant women. Malaria infection is more common in pregnancy because during pregnancy the immune system of pregnant women decreases so that they are more susceptible to infection. Pregnant women with malaria have a risk of anemia and death. This type of research is quantitative with a cross sectional design. The population is 176 people, while the sample is 176 people, the sampling technique is exhaustive sampling. The data collection instrument used a recording sheet. Data processing was carried out using the SPSS program, statistical test used chi square at = 0.05. The results showed that there was a relationship between anemia and malaria in pregnant women in the Waena Public Health Center with p value (0.003 <0.05). This study recommends pregnant women to maintain food intake, especially those containing iron.